Peningkatan Pengalaman Belajar Siswa Melalui Pendampingan Pembelajaran Tematik Di SD Negeri 12 Pemecutan - Jaya, Ketut Manik Asta; Wahyuni, Ni Nyoman Tri; Setiawati, Gusti Ayu Dewi; Pastika, Gede Tilem Pastika; Yasa, I Made Wiguna (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This article discusses community service involving thematic learning assistance during limited face-to-face learning at SD N 12 Pemecutan. The activities focused on thematic learning in Grade V aim to educate students and provide them with new learning experiences, improve the quality of education, and enhance the overall educational standards during limited face-to-face learning. The thematic learning assistance provided by the team includes the creation of a work program designed to stimulate and address the difficulties faced by Grade V students at SD N 12 Pemecutan. The team's focus for thematic learning assistance is on subjects such as Civics, Mathematics, Indonesian Language, and Science. In addition, the community service team also teaches Yoga exercises that can be immediately practiced by students to promote their health. The team has also introduced a technology-based learning program to enhance students' knowledge, utilizing applications like Quiziz and instructional videos. Furthermore, the team has developed a work program aimed at optimizing the school's facilities and infrastructure. Based on all the activities conducted, significant changes have occurred in the teaching and learning process at SD N 12 Pemecutan, which is the location of this community service.